Geology, Structure, Metamorphism and Deformation of Botechaur-Chaurjhari Area of Western Nepal - Kadel, Sushma; Paudyal, Kabi Raj (Bulletin of the Department of Geology, 2022)
The Lesser Himalayan unit of the Nepal Himalaya, especially the western and central parts comprise numerous metamorphic crystalline thrust sheets occupying the cores of large synclinorium. Despite having complex geological settings, some areas in western parts of Nepal lack detailed geological mapping with credible information. This study aims to explore one least explored section; with emphasis on lithostratigraphy, structural setting, deformation, metamorphism, and magmatism. Detailed geological mapping along the Botechaur-Chaurjhari section revealed three tectonostratigraphic units separated by the Main Boundary Thrust (MBT) and the Mahabharat Thrust (MT); the Siwaliks (Middle Siwalik), autochthonous units of the Lesser Himalaya (Dandagaon Phyllite, Nourpul Formation and Dhading Dolomite) and the Lesser Himalayan Crystalline units (Kalagaon Formation and Chaurjhari Formation) from south to north respectively. From the microstructural analysis and measurements of shear sense indicators, the MT shows a top-to-the-south sense of shear indicated by asymmetric boudins, parasitic folds, and thrusting indications in blasto-mylonitic augen gneiss and asymmetric porphyroblast of garnet and the shearing in the garnet. The area also displays an inversion of metamorphism, supporting the development and existence of thrust. The metamorphic grade ranges from chlorite grade to kyanite grade having metamorphic facies assemblage of zeolite to amphibolite facies. Five phases of deformation (D1 to D5) are prevalent within the area, two of which (D1 and D2) belong to the pre-Himalayan (pre-Tertiary) orogeny and the rest of the deformation syn-to post-Himalayan.